Accreditation Repository Architecture for Higher Education Document Management (International Journal of Applied Research and Innovation, 2026)
Accreditation document management in higher education requires a system architecture that can maintain accuracy, traceability, and document accountability. This study analyzed the architecture of a web-based accreditation repository to optimize higher education document management. The research used a software engineering approach involving literature review, observation, interviews, document analysis, business process mapping, Unified Modeling Language modeling, Extreme Programming-based prototyping, black box testing, and scenario-based functional validation. The findings showed that the proposed repository architecture consists of user, interface, application service, data and document, and output layers. The developed SIPADOK prototype supported login, role-based access control, LKPS category management, document upload and preview, reviewer assignment, progress monitoring, and PDF or Excel report export. Functional testing showed that the main scenarios worked according to the expected behavior. The study indicates that document optimization is not determined only by file digitization, but also by the integration of data architecture, review workflow, access control, document status, and reporting outputs..